Role of Nongovernment Organisations in the Development of the Kosovar Society - Hoti, Hamdi; LIMAJ, Demir; KURHASKU-HOTI, Edisona (European Journal of Sustainable Development, 2020)
Generally, the paper shows the importance that have non-government organization in Kosovo on development routes toward democratic and transparent society. Today, the main purpose of NGO’s is creating a better life for society by researching for the needs of society and fulfilling these requirements in the near future. Today, in day life we are facing with different individual and groups of society and is being questioned about the purpose of the works of these organizations. Research results of the paper shows that NGO’s have played and are playing positive important role in Kosovar society development, in generally developing in /special fields. Among the main requirements include cooperation and coordination between NGO’s to achieve powerful impact in society development and increasing transparency for the public and creating reliability that it will not misused taken fonds and have the main mission improvement of society instead of benefits.